Seroprevalence of Trichinella Spp. in Pigs and Knowledge, Attitude and Practices of Pig Farmers of Eastern and Midwestern Regions of Nepal - Kathayat, Dipak; Shrestha, Swoyam P.; Dhakal, Santosh; Ghimire, Laxman; K.C., Mahesh (International Journal of Applied Sciences and Biotechnology, 2015)
A cross-sectional study was conducted on four major pig raising districts of eastern and mid-western region of Nepal from February to May 2014 to find out the seroprevalence of Trichinella spp. A total of 184 serum samples of pigs were collected and antibodies against trichinella were detected using ID screen trichinella indirect multi- species ELISA kit. The study revealed prevalence rate of 3.8% and difference in prevalence rate according to age, sex, breed, rearing system, ecozone, region & district were statistically insignificant (P>0.05) as analysed by Chi-square test using PHStat version 2.5 and Fisher’s exact test. This study confirms that antibodies of Trichinella spp. are circulating in pigs of Nepal. Further, the knowledge, attitude and practices survey of meat borne helminthic zoonoses was conducted among 50 pig raisers and pork consumers by face to face interview using a semi-structure questionnaire. This survey concludes that although there were significant portion of the respondents aware of meat borne helminthic zoonoses but there were still a noticeable proportion of respondents who didn’t have a proper knowledge that upsurge public health risks. Moreover, present-day situation of their pig raising practices & pork consumption system possess them to a menace of public health zoonoses. be done for enhancing the potential of isolates. Int J Appl Sci Biotechnol, Vol 3(3): 402-407